Assessment of a Medical Student–Run Multidisciplinary Oncology Shadowing Program - Marco Santos Teles; Shrey B. Shah; Malcolm D. Mattes (Journal of Cancer Education, 2025)
Clinical exposures during the first two years of medical school (MS1-2) provide students an opportunity for early networking, mentorship and career exploration. The feasibility and perceived value of an extracurricular, student-run multidisciplinary oncology shadowing program was evaluated in this study. At a single institution, an oncology interest group collaborated with oncologists to create a shadowing program for MS1-2 students. Three radiation oncology (RO), two medical oncology (MO), and four surgical oncology (SO) faculty participated. A quarterly sign-up form was emailed to all MS1-2 students with available shadowing sessions. Electronic surveys were sent to students (after shadowing) and faculty (after 18 months of program operation) with multiple choice and 5-point Likert-type (1 = low, 5 = high) questions about their experiences. A total of 57 of the 97 participating students, and all 9 of the 9 participating faculty, responded to surveys (response rates 59% and 100%, respectively). Thirty students (53%) shadowed in RO, 23 (40%) in SO, and 4 (7%) in MO. Most students were very satisfied with their interactions with faculty (mean Likert-type rating of 4.14 ± standard deviation 0.85) and their overall experience compared to prior shadowing experiences (3.84 ± 0.85). Fifty-four students (96%) would recommend the experience to a classmate. Four faculty (44%) reported much more shadowing than before. Seven faculty (78%) felt the experience was best when residents or fellows were also present. All physicians planned to continue participating. This study demonstrated that a student-run, oncology shadowing program was feasible to implement, and viewed favorably by faculty and student participants.